Effect of Dietary Nitrate and Anthocyanins on Anaerobic Exercise in Untrained Individuals. (29th May 2020) - Tsai, Paul; Huang, Yun Chieh; Sanchez, Aurora; Noval, JeJe; Bains, Gurinder; Bradley, Bruce; Mleziva, Pablo; Wilson, Christine; Oda, Keiji; Bitok, Edward
Abstract: Objectives: The purpose of this study was to examine the effects of dietary nitrate and anthocyanins on exercise performance in healthy untrained individuals. Methods: In a randomized double-blind crossover study, six men (mean age 24.3 y) and 23 women (mean age 24.1 y) were randomly assigned to Treatment A (5.05 g beetroot powder + placebo/d) or Treatment B (5.05 g beetroot powder + 480 mg tart cherry/d) for seven days. Each treatment was followed by a seven-day washout after which subjects switched treatments. At the end of each treatment period, subjects performed a modified Wingate Anaerobic Test on a Monark 928E bike. Data on speed (RPM), power (watts), and heart rate were collected and analyzed using linear mixed models adjusted for baseline subject characteristics, treatment sequence (A-B, B-A), energy (kcal), and sleep (hours). Results: Average heart rate during the first five seconds of the cycling sprint was significantly lower after treatment A than after treatment B (−1.6 to 2.7 BPM, P < 0.05). Participants pedaled five meters further after treatment B compared to treatment A ( P = 0.25). No significant differences were observed between treatments on RPM and blood pressure. Conclusions: Supplementation with beetroot and tart cherry powder for seven days may improve anaerobic exercise performance by maximizing potential heart rate and energy output in untrained individuals. Funding Sources: The study was sponsored by the School of Allied Health Professions, Loma Linda University.